A Pyridazinone Compound for Effectively Treating Non-alcoholic Steatohepatitis by Targeting THRβ - Cheng, Hao; Wang, Xiao-Bo; Zhi, Ying; Liu, Bo; Liu, Na; Li, Meng-Jun; Mu, Yan-Ling (Frontiers in Chemistry, 2022)
Developing effective therapies and medicines to conquer Non-alcoholic steatohepatitis (NASH) is of great significance for public health and faced with major challenge. The activation of thyroid hormone receptor agonist THRβ could be regulated by target drugs that has brought huge potential to the treatment of NASH. In this work, pyridazinone compound YWS01125 was synthesized for the first time. In this study an ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for YWS01125 determination was established and the pharmacokinetics of YWS01125 was evaluated. The results showed that liver microsomes stable and have not metabolized, the t1/2 was 189.12 ± 95.27, 152.64 ± 37.98 and 181.95 ± 64.25 min, respectively and the tissue distribution studies demonstrated that YWS01125 was quickly distributed to various tissues. With successful application in the pharmacokinetics study of YWS01125, the UPLC-MS/MS method has shown its characteristics of high sensitivity, rapidity, good selectivity.